PENGARUH KEPERCAYAAN DAN RESIKO TERHADAP KEPUTUSAN PELANGGAN BELANJA MELALUI SISTEM INFORMASI PENGADAAN SEKOLAH (SIPLAH) PADA PERUSAHAAN CV.TIA MEDAN SUMATERA UTARA - Br Hasibuan, Juli Malem; Nasution, Lukman (JURNAL MANAJEMEN AKUNTANSI (JUMSI), 2021)
This study aims to determine the effect of trust and risk on the decision of customers shopping through SIPLah on CV.TIA. Data analysis method used is descriptive and quantitative. The population in this research is customer CV TIA that shopping through SIPLah in particular are a few schools in North Sumatra as much as 230 school. the sample in this study was set as much as 70 respondents. This research was conducted at the Company CV TIA, which is located in jalan Menteng VII Gg. Self-Sufficiency No.28 Kecamatan Medan Denai, Medan, North Sumatra 20228. The research starts from December 2020 to June 2021. The results of this study show that trust partially positive and significant effect on the decision of customers shopping through the Information System the Procurement of School (SIPLah) on CV. TIA Medan, North Sumatra. The risk for partial negative effect not significant to the decision of customers shopping through the Information System the Procurement of School (SIPLah) on CV. TIA Medan, North Sumatra. Trust and risk simultaneously have a positive and significant impact on the decision of customers shopping through the Information System the Procurement of School (SIPLah) on CV. TIA Medan, North Sumatra. The variables of trust and risk to explain its influence on the decision of customers shopping through the information system the procurement of school (SIPLah) on CV. TIA Medan, North Sumatra by 76,3% while the rest 23,7% is explained by other factors examined in penleitian such as variable variable security, quality of service and product quality.